Immune system changes in the pathogenesis of neurofibromatosis type 1 - R. N. Mustafin (Онкогематология, 2022)
Neurofibromatosis type 1 (NF1) is a hereditary tumor syndrome occurring with a frequency of 1: 3000 of the population. NF1 is caused by germline heterozygous mutations in the NF1 gene, which encodes the oncosuppressor neurofibromin. The disease has a specific progressive course with multiple neurofibromas, in the initiation and growth of which NF1+/ – mast cells, macrophages and lymphocytes play an important role. Accordingly, the deficiency of neurofibromin impairs the differentiation and correct functioning of immune system cells. This is evidenced by the increased risk of leukemia in patients with NF1 and the role of NF1 mutations in the development of sporadic hematological malignancies. The development of neurofibromas is associated with the fact that NF1–/ – Schwann cells stimulate the migration of mast cells into the tumor microenvironment, which actively degranulate. The released cytokines promote neoangiogenesis, inflammation, fibroblast proliferation and the production of excess collagen. Therefore, in the treatment of NF1, the use of ketotifen and a kit/ fms kinase inhibitor is recommended. Macrophages and T-lymphocytes in neurofibromas do not provide an antitumor response, but promote inflammation and tumor growth. They produce STAT3 (signal transducer and activator of transcription 3), TGF-β, EGFR, IL-6, IL-4, and PD-1. Therefore, a promising direction is NF1 therapy with STAT3 inhibitors and immune checkpoint inhibitors that block programmed cell death ligand 1 (PD-L1). Activation of MEK signaling pathways in NF1 leads to PD-L1 stimulation; therefore, MEK inhibitors, which also suppress the RAS/RAF/MEK/ERK system, turned out to be effective in the treatment of NF1. For the treatment of sporadic malignant neoplasms, in the development of which NF1 mutations play a role, the developed methods of NF1 therapy can be used.